New fossil rhopalids (Heteroptera: Coreoidea) from the Middle Jurassic of Inner Mongolia, China - Yao, Yunzhi; Cai, Wanzhi; Ren, Dong; Shih, Chungkun (Zootaxa, 2006)
Three new genera and three species of fossil rhopalid, Originicorizus pyriformis gen. & sp. nov., Quatlocellus liae gen. & sp. nov., and Grandicaputus bipunctatus gen. & sp. nov., are described and illustrated. They were discovered from the Middle Jurassic Jiulongshan Formation of Eastern Inner Mongolia, China. The present discovery demonstrates that the early diversification of rhopalids was well underway by the Middle Jurassic.